New technologies for the treatment of people with autism in Peru: analysis from the teaching experience - Loconi Guerra, Liliana (2017)
The present article first addresses the general aim of education and the use of new technologies, then addresses the specific case of education for people with autism spectrum disorders (ASD). Then, the specific case of special education in Peru and the use of these new technologies, considering the experience as a teacher in two schools of special educacion –one private and public–, are addressed and it finishes with a brief discussion and conclusions.